THE IMPACT OF INSTANT RED GINGER PRODUCT PACKAGING DEVELOPMENT ON CONSUMER BUYING INTEREST (CASE STUDY AT P4S MENOREH HERBAL) - Ambarwati, Dewi Leilani (Universitas Suryakancana, 2024)
The purpose of this research was to determine the effect of packaging development on consumer buying interest in instant red ginger products at P4S Menoreh Herbal. This research was conducted in January - May 2024 at P4S Menoreh Herbal, Salaman, Magelang, Central Java. The determination of research locations and sampling techniques was carried out by purposive sampling method. The number of samples was 40 respondents who visited and tasted instant red ginger products. Data collection techniques used observation, interviews, and questionnaires. Packaging development was done through the information stage, screening stage, and creative stage. There are 3 sub-dimensions in packaging design which include graphic design, design structure, and product information. Furthermore, testing the effect of new packaging on consumer buying interest with the analysis technique used is multiple linear regression analysis. The results of this research are the packaging preferred by respondents is in the form of a standing pouch with aluminum foil material, white in color, and contains product information consisting of composition, expiration date, logo and brand, net weight, serving suggestions, and manufacturer's address. The results of data analysis and hypothesis testing show that the variables of graphic design, design structure, and product information simultaneously and partially affect consumer buying interest.